MAKNA JILBAB GAUL - Midya Boty (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
The paper tries to uncover the meaning and the factors of “Hijab Gaul” (Slank Hijab), modern style of Hijab” for higher students. Hijab is not only as an identity for muslim women as a devotion to Islamic teaching and the symbol of piety, it also the fashion. The paper use qualitative method that reveals he meaning of people behavior in social context. The paper finds that there are variations of the meaning of Hijab for higher students as (1) the symbols of identity (2) lifestyle (3) social statuse (4) symbol of personality (5) symbol of peaceful personal tranquility.